CHEST WALL RESECTION FOR LOCOREGIONAL RECURRENCE OF BREAST CANCER: A FEASIBLE AND EFFECTIVE - Mota, Bruna Salani; Piato, Jose Roberto; Abrão, Fernando Conrado; Dória, Maíra Teixeira; Ricci, Marcos Desidério; Munhoz, Alexandre Mendonça; Filassi, Jose Roberto (Mastology, 2019)
Objective: The aim of this study was to evaluate survival after chest wall resection for breast cancer locoregional recurrence. Secondary endpoints were symptomatic control and safety of the procedure. Method: This was a retrospective review including all patients who underwent chest wall resection for breast cancer local recurrence at the Division of Thoracic Surgery of the School of Medicine of São Paulo University, from January 1998 to November 2011. Full thickness chest wall resection involving bones and/or soft tissues was performed to achieve macroscopical free margins. Results: Eighteen patients were included in this study with a mean followup of 83.5 months. The interval between mastectomy and chest wall recurrence (CWR) was 4.2 years (0.5 to 9 years). The resection was complete in 12 patients (66%) and incomplete in 6 (33%), in whose resection would involve amputation of an upper limb. Mean tumor size was 8.25 cm and resection of the costal arch was necessary in 10 patients. There was no operation death and after two years, 66% of patients were alive. Six patients died due to distant recurrence of breast cancer on patients who died to inflammatory acute abdomen. The mean survival among patients who died was 25.2 months (12 to 42 months). At the last follow-up visit, eleven patients were alive. Conclusion: CWR for locally recurrent breast cancer is feasible and safe in selected patients, who did not develop metastatic disease, allowing good quality of life for a considerable period. Larger and prospective series are needed to endorse our findings.